PEMBELAJARAN ANSAMBEL MUSIK MEMPERSIAPKAN ANAK DIDIK MEMASUKI ABSTRACT MASYARAKAT MULTIKULTURAL - Kun Setyaning Astuti (Jurnal Cakrawala Pendidikan, 2003)
Globalization is a reality. It is one of the consequences .ofglobalization that there has been a cultural transformation which, inturn, forms a multicultural society. Entering the global world withno cultural identity, one would only get lost among the powerfulcultures. This writingis an attempt to explain the importance of .teaching and learningthe musical ensemble as an effort, amongothers, to prepare studentsfor their entrance into the multiculturalsociety.This writing triesto describe some phenomena andconsequencesof globalization. Based on some literature, the writertries to explain someof the competencies necessary for an individualto live in the global world. Education as the basis for shapingpersonality can prepare students for that; so oneof the efforts isproviding ensemble music lessons.A musical ensemble has similarities with a multiculturalsociety in termsof their condition and demand. Both demandindividual and cooperative skills. Besides, bothof them are alsosupportedby individuals with different roles'and responsibilities